Integrated static code analysis and runtime verification. (19th August 2014) - Sözer, H.
Summary Static code analysis tools automatically generate alerts for potential software faults that can lead to failures. However, these tools usually generate a very large number of alerts, some of which are subject to false positives. Because of limited resources, it is usually hard to inspect all the alerts. As a complementary approach, runtime verification techniques verify dynamic system behavior with respect to a set of specifications. However, these specifications are usually created manually based on system requirements and constraints. In this paper, we introduce a noval approach and a toolchain for integrated static code analysis and runtime verification. Alerts that are generated by static code analysis tools are utilized for automatically generating runtime verification specifications. On the other hand, runtime verification results are used for automatically generating filters for static code analysis tools to eliminate false positives. The approach is illustrated for the static analysis and runtime verification of an open‐source bibliography reference manager software. Copyright © 2014 John Wiley & Sons, Ltd.